Cost-effectiveness of peer role play and standardized patients in undergraduate communication training - Bosse, Hans-Martin; Nickel, Martin; Huwendiek, Sören; Schultz, Jobst-Hendrik; Nikendei, Christoph (BMC medical education, 2015)
The few studies directly comparing the methodological approach of peer role play (RP) and standardized patients (SP) for the delivery of communication skills all suggest that both methods are effective. In this study we calculated the costs of both methods (given comparable outcomes) and are the first to generate a differential cost-effectiveness analysis of both methods.
Gesehen am 27.05.2020